Clinical profile of leprosy patients: A prospective study - Sejal Thakkar; Sangita V Patel (Wolters Kluwer Medknow Publications, 2014)
Introduction: Early diagnosis and early adequate drug treatment is very important aspect to reduce the load in cases of leprosy. So, correct labeling of paucibacillary and multibacillary cases is a prerequisite for the adequate treatment. Confirmation of diagnosis is an important indication for histopathological examination in doubtful cases. Objectives: The present study was carried out to know the clinical profile of leprosy patients, concordance between clinical and histopathological diagnosis in cases of leprosy, and to assess the therapeutic efficacy of antileprosy therapy. Study Design: Two hundred and fifty clinically diagnosed leprosy patients attending skin outdoor patient department (OPD) were included in the study. Slit skin smear was performed in all the cases. In that case concordance between clinical and histology can be determined only in 30 cases. All the patients were treated with MDT (multidrug therapy) as per WHO guideline. Results: A total of 250 patients attended the clinic with male to female ratio of 1.7:1. The highest incidence was noted in 17-40 years of age group. In the clinical disease spectrum, 40% patients were in the borderline spectrum followed by tuberculoid leprosy (TT) (29.2%), lepromatous leprosy (LL) (26.8%), and 3.9% of indeterminate leprosy (IL). A total of 18% of patients were of primary neuritic leprosy. A total of 8.3% patients had definite history of contact in the family or neighborhood. Clinicopathological correlation was noted in 60% of patients with maximum disparity (52.9%) in the borderline group of patients. A total of 52.8% were MB (Multibacillary) and 47.2% were PB (Paucibacillary) cases. Morphological index became negative after 6 months in all patients. Mean fall of bacteriological index after 6 months was 0.19, while after 1 year, it was 1.05. Conclusion: Timely diagnosis and adequate treatment of cases with MDT is most effective. Histopathological examination is must in doubtful cases of leprosy.